A arte de si na dança tribal: narrativas entre espiritualidade e corpo cênico - Bezerra, Kilma Farias (2017)
This research seek to understand possible links between spirituality and the performing body from written and danced narratives built by Tribal Brazil dancers. The proposition stands in support of educational activities between teaching in the field of dance, and Religious Studies, seeking a dialogue between them. The research fiels was provided by a courseon Tribal Brazil taught by the researcher composed of two groups of students. Live and remote, from which were selected 9 students to be observed in depth. The proposal was to observe IF the act of dancing is able to operate transformations in the subjectivity of these students and if this experience is capable of changing their stage presence. When thinking on the historical and theoretical foundations of Tribal Brazil, issue such as body, individual and collecive memory, the care of yourself, movement, stage presence and non-religious spiritualities are brought. The methodological approach starts from understanding spirituality in Foucault (1926-1984) and consisted of three pillars: performative researchs ou guided by practice, Laban movement analysis (18791958) and ethnography as method.